2008
DOI: 10.1097/ta.0b013e31809fec16
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Outcome After Orthopedic Trauma

Abstract: This study has highlighted pain and PTSD symptoms as frequent and disabling factors after othropedic trauma. There is clearly a need to focus on alleviating these problems as part of the rehabilitation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
119
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 17 publications
5
119
1
1
Order By: Relevance
“…Pain and psychological distress are interrelated and negative emotions tend to be elevated during the early postinjury period [3,21,37,43,66]. Thirty-eight percent of our patient population reported clinically significant depressive symptoms, which is consistent with other studies that have reported depression rates of 30% to 40% in the hospital and during the early postoperative period in patients with traumatic injury [3,15,45]. We also found a moderate relationship between depressive symptoms and decreased physical health at 1 year.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…Pain and psychological distress are interrelated and negative emotions tend to be elevated during the early postinjury period [3,21,37,43,66]. Thirty-eight percent of our patient population reported clinically significant depressive symptoms, which is consistent with other studies that have reported depression rates of 30% to 40% in the hospital and during the early postoperative period in patients with traumatic injury [3,15,45]. We also found a moderate relationship between depressive symptoms and decreased physical health at 1 year.…”
Section: Methodssupporting
confidence: 81%
“…Trauma survivors also experience profound levels of physical disability and difficulty returning to productive employment [7,34,35]. Patient-reported quality-of-life scores are consistently below the health norm for adult populations [22,58], 40% to 50% report moderate levels of disability [1,7], and 35% to 50% have delayed return to work up to 24 months after injury [7,39,45].…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with our findings with a wide range of problems reported by patients following pelvic fractures. In a study by Ponsford et al 16 on various severe orthopaedic trauma patients, 113 patients out of 342 eligible consenting participants, were recruited during rehabilitation and followed for two years. Their results indicated the presence of very significant levels of disability in all domains of the SF-36 at one and two years in their patients, 93% of whom were injured in motor vehicle accidents.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 45% of the patients could not pursue with leisure activities and 27% reported a broken marriage six years after trauma 19 . Furthermore, pain was found to be a major predictor for psychological adjustment problems two years after injury 16 . ASD, PTSD, and psychological distress are positively associated with wound healing and fatigue 13,[20][21][22][23][24][25] and negatively with quality of life (QOL) compared to the general population 18,[26][27][28][29][30][31] .…”
mentioning
confidence: 99%
“…Psychosocial problems and disorders can have a negative impact on patients' lives up to years later 13,[16][17][18] . For instance, 45% of the patients could not pursue with leisure activities and 27% reported a broken marriage six years after trauma 19 .…”
mentioning
confidence: 99%